From Adoption to Productivity: The Central Role of Optimal Technology Use in The Informal Economy - Mizan Ikhlasul Rahman; Chairul Sa'roni; Sri Hidayah; Muhammad Fathur Reza (Jurnal Ilmiah Manajemen & Bisnis, 2026)
This study examines factors influencing optimal technology use and its relationship with technology adoption and business performance in the informal economy. It highlights the need to explore ways in which technology can maximize productivity and performance. Most studies have documented the discourse on technology adoption and its drivers, while the drivers or factors that facilitate optimal technology use remain comparatively underexplored. Thus, this study fills the gap. This study addresses the question: What factors influence optimal technology use, and how does it mediate the relationship between technology adoption and business performance? It also emphasizes that directly eradicating or formalizing the informal economy is not an ideal solution. Mixed methods were employed in this study. PLS-SEM analysis was conducted using SEMinR in RStudio, based on data from 221 completed questionnaires, providing reliable empirical evidence. Thematic analysis was also applied to qualitative responses to provide additional insights. Quantitative and qualitative evidence confirms significant relationships among technology adoption, technology use, and business performance. All indicators significantly impact their respective constructs, supporting the hypothesized relationships. Optimal use of technology partially mediates the positive and significant impact of adoption on business performance. Key factors, such as technology adoption and user commitment to continuous learning, are essential to optimizing technology use. Practical strategies include allocating adequate resources for ongoing training and skill development and ensuring the technology aligns with operational needs to enhance efficiency.